Physical condition of pupils of pre-school educational establishments of different types - N.V. Moskalenko; V.G. Savchenko; A.V. Polyakova; O.S. Mikitchik; O.O. Mitova; V.V. Griukova; A.V. Mytsak (IP Iermakov S.S., 2020)
The purpose of the study is to determine the physical condition of the pupils of pre-school educational establishments of various types for improving the quality of the educational process of physical education. Material and methods . The study involved 3-4 year-old children. The children attended preschool institutions of various types in the city of Dnipro. They were the children's educational establishment №282 of the combined type, the children's educational establishment №192 of the sanatorium type, the children's educational establishment №28 of the compensating type, children's educational establishment №244 and №404 of general development. Control (n = 90) and experimental (n = 95) groups were created in each age group of a particular type of institution. The differentiation of pupils of institutions of different types into two subgroups was caused by their differences in functional indicators and health status. At the beginning of the experiment, the homogeneity of the studied groups of children was noted (p> 0.05). Results. The model of organization of rational motor mode of 3-4 year-old children has been substantiated and developed. Organizational and methodological bases of realization of the model of rational motor mode of 3-4 year-old children in preschool educational institutions of various types have been developed. The influence of the developed model on the physical condition of pupils of pre-school educational institutions of different types has been determined. The study of the anthropometric parameters of children after the implementation of the developed model showed no differences in these parameters. These differences were observed in children of different types of kindergartens in all sex-age groups. The determination of functional abilities of children resulted in a significant improvement in spirometry, respiratory rate, heart rate, Ruffier test in experimental groups of children of both sexes (p <0.05). The indicators of the functional state of the cardiovascular system and physical performance of the pupils of preschool educational establishments of the sanatorium type and the compensating type were lower than the similar indicators of the pupils of general development establishments. The indicators of heart rate of real rest and respiratory rate of children of experimental groups of institutions of the sanatorium and compensating type corresponded to the average level. Conclusions. The obtained result of this empirical study confirms the hypothesis that the organization of rational movement mode for 3-4 year-old children contributes to improving of their physical condition. The obtained results indicate the improvement of the quality of the educational process of physical education of children in pre-school educational establishments of different types.